2013
DOI: 10.1123/jcsp.7.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depressive Symptoms and Correlating Variables Among German Elite Athletes

Abstract: Depression among elite athletes is a topic of increasing interest, but empirical data are rare. The present study aimed to provide insight into the prevalence of depressive symptoms among German elite athletes and possible associated factors. In an online survey of 162 athletes, we explored depressive symptoms, chronic stress, coping strategies and stress-recovery states. Results indicated an overall prevalence of 15% for depression among elite athletes (n = 99), and revealed higher levels of depressive sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
110
3
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(135 citation statements)
references
References 29 publications
11
110
3
11
Order By: Relevance
“…And indeed, whether one takes into consideration the important tournaments and potential sporting injuries (acute stress) or the frequency of tournaments and training sessions (chronic stress), the life of an athlete can be regarded as "stressful". Nixdorf et al (2013) found support for this assumption, indicating high associations between chronic stress and depressive syndromes, as well as between different coping strategies and depressive syndromes in elite athletes. But which are the main stressors, connected to experiences of chronic stress and depressive syndromes?…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…And indeed, whether one takes into consideration the important tournaments and potential sporting injuries (acute stress) or the frequency of tournaments and training sessions (chronic stress), the life of an athlete can be regarded as "stressful". Nixdorf et al (2013) found support for this assumption, indicating high associations between chronic stress and depressive syndromes, as well as between different coping strategies and depressive syndromes in elite athletes. But which are the main stressors, connected to experiences of chronic stress and depressive syndromes?…”
Section: Introductionsupporting
confidence: 53%
“…Regarding the population of athletes in elite sports, stress is also discussed in relation to depressive syndromes according to Puffer & McShane (1992). Recent results (Nixdorf, Frank, Hautzinger, & Beckmann, 2013;Schaal et al, 2011) indicate that prevalence rates between 4% and 15% in elite athletes seem comparable to the general population in Europe (cf. .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies focused on college athletes in the USA, [12][13][14][15][16][17][18] and few investigated the top-level national athletes. [19][20][21] Many studies included athletes from various sports without providing prevalence data for specific types of sport. 12 13 17-20 22 Up to now, only one study reported mental health problems of active high-level male football How might it impact on clinical practice in the near future?…”
Section: Introductionmentioning
confidence: 99%
“…Further, significantly higher average depression scores were observed in individual rather than in team sport athletes. 20 Thus, differences in the athletes' characteristics may have contributed to the heterogeneous results in addition to the methodological problems mentioned above. Very little information about the prevalence of anxiety in active athletes was found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 17 and Wolanin et al 14 showed substantial differences between sports (see table 1). Further, differences in the prevalence rates of depression have been reported between professionals, junior and amateur athletes,18 between adult and U-17 football players,10 as well as between different playing positions10 20 and level of play 10 20. Injured players have usually higher depression rates than uninjured players 6 21 22.…”
Section: Introductionmentioning
confidence: 99%